Compliance with Personal Protective Equipment Usage among Finishing Section Workers in a Public Housing Project, Jakarta - Hutapea, Selly Mariati; Lestari, Putri Winda (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2025)
The control hierarchy must be implemented properly in construction. One of the control hierarchies is the use of Personal Protective Equipment (PPE). Based on field observations, there are still finishing workers in the Flats Project who do not use PPE. The purpose of this study was to determine the factors associated with compliance with the use of PPE for workers in the finishing section of the Flat Project. It is a cross-sectional study. The sampling technique is total sampling (40 people). Data was gathered through observation and the completion of a questionnaire. Univariate and bivariate Chi-Square tests were used to analyze the data. The results showed that the factors related to compliance with the use of PPE were knowledge (p=0.017), supervision (p=0.010), sanctions (p=0.010), while the variables not related to compliance with the use of PPE were education level (p=0.293) and age (p=0.510). It is essential to enhance workers’ knowledge, strengthen supervision, and enforce strict sanctions to improve compliance with PPE use.